Influencia del deficiente soporte familiar en la calidad de vida del adulto mayor del programa “amigos de la salud” del hospital de apoyo Chepén – provincia de Chepén: 2017. - Imán Max, Susy Cynthia (2018)
This thesis was carried out with the aim to explain the influence of family support in the quality of life of the Older Adults Program "friends" of the Hospital Support Chepen - Province of Chepen: 2017. It has been considered the type of applied research, on the basis of an explanatory design, has used the methods and techniques of quantitative and qualitative research, the sample consisted of 44 older adults belonging to the program designated as the unit of analysis. The results obtained show that older adults program suffer from emotional neglect (66 %), and discontinuation material (55 %) of part of their family, because it does not receive financial support and emotional well-being of your family. In addition, there are moral in a situation of abandonment, because they do not receive affection of his family, not on their basic needs, at the same time, express that their children are not visit and do not support them in their health care. With this research we intend to provide information to the Area of Social Well-being of Hospital Support Chepen, to implement programs directed to the families and institutions benefactors for the solution of this social problem.